Real-time imaging of density ducts between the plasmasphere and ionosphere - Loi, S.; Murphy, T.; Cairns, I.; Menk, F.; Waters, C.; Erickson, P.; Trott, C.; Hurley-Walker, Natasha; Morgan, John; Lenc, E.; Offringa, A.; Bell, M.; et al. (American Geophysical Union, 2015)
Ionization of the Earth's atmosphere by sunlight forms a complex, multilayered plasma environment within the Earth's magnetosphere, the innermost layers being the ionosphere and plasmasphere. The plasmasphere is believed to be embedded with cylindrical density structures (ducts) aligned along the Earth's magnetic field, but direct evidence for these remains scarce. Here we report the first direct wide-angle observation of an extensive array of field-aligned ducts bridging the upper ionosphere and inner plasmasphere, using a novel ground-based imaging technique. We establish their heights and motions by feature tracking and parallax analysis. The structures are strikingly organized, appearing as regularly spaced, alternating tubes of overdensities and underdensities strongly aligned with the Earth's magnetic field. These findings represent the first direct visual evidence for the existence of such structures.